2004
DOI: 10.1161/01.str.0000125709.17337.5d
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Comparison of Processes of Care Between Stroke Units and Conventional Care Wards in Australia

Abstract: Background and Purpose-Approximately 23% of Australian hospitals provide Stroke Units (SUs). Evidence suggests that clinical outcomes are better in SUs than with conventional care. Reasons may include greater adherence to processes of care (PoC). The primary hypothesis was that adherence to selected PoC is greater in SUs than in other acute care models. Methods-Prospective, multicenter, single-blinded design. Models of care investigated: SUs, mobile services, and conventional care. Selected PoC were related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 19 publications
6
99
0
1
Order By: Relevance
“…Seven studies (17,24,25,32,34,36,38) had consistent findings whereby adherence to a combination of several KPIs ("bundle") was associated with a greater decrease in stroke mortality. A lower risk for poor outcome was also reported when full stroke care bundle was achieved (25,36).…”
Section: Association Between Adherence To Groups Of Kpis and The Riskmentioning
confidence: 86%
See 1 more Smart Citation
“…Seven studies (17,24,25,32,34,36,38) had consistent findings whereby adherence to a combination of several KPIs ("bundle") was associated with a greater decrease in stroke mortality. A lower risk for poor outcome was also reported when full stroke care bundle was achieved (25,36).…”
Section: Association Between Adherence To Groups Of Kpis and The Riskmentioning
confidence: 86%
“…18 The majority (23/30) Coma Scale (36), while the remainder used stroke severity proxies such as level of consciousness, incontinence, dysphagia, dysphasia, paralysis, and disability.…”
mentioning
confidence: 99%
“…We considered the structural indicators (setting and staffing) as well as the performance indicators (process of care and diagnostic availability) because both types of parameters could influence the patient's outcome [34,35]. Adherence to a process of care was evaluated in SUs with respect to stroke teams in single unit trials [36] and in SUs with respect to mobile teams or conventional care in a multicentre cohort study [8]. These two studies demonstrated that a closer adherence to a well defined process of care explains the effectiveness of SU hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, despite the meta-analysis providing evidence in favour of the comprehensive SU model, SUs currently implemented vary significantly in structure and organisation [4][5][6][7]. Randomised clinical trials and other research have been used to evaluate the efficacy of the individual elements of care that would improve stroke patient outcomes [4,[8][9][10][11][12]. But clear evidence of the relative efficacy for different models combining different structural and performance characteristics is very poor [10].…”
mentioning
confidence: 99%
“…The lack of comprehensive stroke centres capable of delivering the full spectrum of care to clients with stroke, will lead to predictably worse outcomes. Strong evidence exists to support, comprehensive stroke units (Cadilhac et al, 2004;Koton et al, 2005;Ko and Sheppard, 2006;Walsh et al, 2006). These dedicated units with multidisciplinary rehabilitation teams are associated with reductions in length of stay at hospitals, healthcare costs, death, and dependency, while improving functional outcomes compared to other stroke unit models (Anderson et al, 2000;Moodie et al, 2006;Chan et al, 2013).…”
Section: Interventionsmentioning
confidence: 99%